Growth Inhibitory Efficacy of Chinese Herbs in a Cellular Model for Triple-Negative Breast Cancer - Nitin T. Telang; Hareesh B. Nair; George Y. C. Wong (MDPI AG, 2021)
Triple-negative breast cancer (TNBC) is characterized by the absence of estrogen receptor-α progesterone receptor and human epidermal growth factor receptor-2. Treatment for this breast cancer subtype is restricted to multidrug chemotherapy and survival pathway-based molecularly targeted therapy. The long-term treatment options are associated with systemic toxicity, spontaneous and/or acquired tumor resistance and the emergence a of drug-resistant stem cell population. These limitations lead to advanced stage metastatic cancer. Current emphasis is on research directions that identify efficacious, naturally occurring agents representing an unmet need for testable therapeutic alternatives for therapy resistant breast cancer. Chinese herbs are widely used in traditional Chinese medicine in women for estrogen related health issues and also for integrative support for cancer treatment. This review discusses published evidence on a TNBC model for growth inhibitory effects of several mechanistically distinct nontoxic Chinese herbs, most of them nutritional in nature, and identifies susceptible pathways and potential molecular targets for their efficacy. Documented anti-proliferative and pro-apoptotic effects of these herbs are associated with downregulation of RB, RAS, PI3K, and AKT signaling, modulation of Bcl-2/BAX protein expressions and increased caspase activity. This review provides a proof of concept for Chinese herbs as testable alternatives for prevention/therapy of TNBC.